Extremely precise age and metallicity of the open cluster NGC 2506 using detached eclipsing binaries. Issue 1 (21st September 2020) - Knudstrup, E; Grundahl, F; Brogaard, K; Slumstrup, D; Orosz, J A; Sandquist, E L; Jessen-Hansen, J; Lund, M N; Arentoft, T; Tronsgaard, R; Yong, D; Frandsen, S; et al.
ABSTRACT: Accurate stellar parameters of stars in open clusters can help constrain models of stellar structure and evolution. Here, we wish to determine the age and metallicity content of the open cluster NGC 2506. To this end, we investigated three detached eclipsing binaries (DEBs; V2032, V4, and V5) for which we determined their masses and radii, as well as four red giant branch stars for which we determined their effective temperatures, surface gravities, and metallicities. Three of the stars in the DEBs have masses close to the cluster turn-off mass, allowing for extremely precise age determination. Comparing the values for the masses and radii of the binaries to BaSTI (a Bag of Stellar Tracks and Isochrones) isochrones, we estimated a cluster age of 2.01 ± 0.10 Gyr. This does depend on the models used in the comparison, where we have found that the inclusion of convective core-overshooting is necessary to properly model the cluster. From red giant branch stars, we determined values for the effective temperatures, the surface gravities, and the metallicities. From these we find a cluster metallicity of −0.36 ± 0.10 dex. Using this value and the values for the effective temperatures, we determine the reddening to be E( b − y ) = 0.057 ± 0.004 mag. Furthermore, we derived the distance to the cluster from Gaia parallaxes and found 3.101 ± 0.017 kpc, and we have performed a radial velocity membership determination for stars in the field of the cluster. Finally, we report on the detection of oscillation signals in γ Dor and δ Scuti members in data from the Transiting Exoplanet Survey Satellite ( TESS ) mission, including the possible detection of solar-like oscillations in two of the red giants.